2021
DOI: 10.1002/jctb.6959
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of peptide linker to amino acid dehydrogenase and immobilized with metal–organic framework

Abstract: BACKGROUND:The metal-organic framework (MOF) ZIF-8 has the advantages of a large specific surface area and high stability. A new strategy for the assembly of amino acid dehydrogenase with peptide linker and for improving enzyme immobilization is proposed.RESULTS: Peptide linker enhanced enzyme activity after immobilization by 138.7%, and maintained 81.2% of its initial activity after seven recycles. The stability of PheDH_1D02/ZIF-8 was greatly enhanced at 70-80 °C and pH 10-11. The catalytic efficiency of Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…HPLC analysis with standard solution of L‐phenylalanine and D‐phenylalanine showed that the peak time of L‐phenylalanine was 25 min, and the peak time of D‐phenylalanine was in 33 min. HPLC detection condition for D/L phenylalanine was as follow: Chromatographic column: Philomon Chirex 3126 (D)‐Penicillamine 250 nm × 4.6 nm, 5 μm; mobile phase, 5% (v/v) acetonitrile and 95% (v/v) 2.0 mM, CuSO 4 aqueous solution; flow rate, 0.8 mL/min; detection wavelength, 254 nm 22 …”
Section: Methodsmentioning
confidence: 99%
“…HPLC analysis with standard solution of L‐phenylalanine and D‐phenylalanine showed that the peak time of L‐phenylalanine was 25 min, and the peak time of D‐phenylalanine was in 33 min. HPLC detection condition for D/L phenylalanine was as follow: Chromatographic column: Philomon Chirex 3126 (D)‐Penicillamine 250 nm × 4.6 nm, 5 μm; mobile phase, 5% (v/v) acetonitrile and 95% (v/v) 2.0 mM, CuSO 4 aqueous solution; flow rate, 0.8 mL/min; detection wavelength, 254 nm 22 …”
Section: Methodsmentioning
confidence: 99%
“…HPLC analysis with standard solution of L-phenylalanine and D-phenylalanine showed that the peak time of L-phenylalanine was 25 min, and the peak time of Dphenylalanine was in 33 min. HPLC detection condition for D/L phenylalanine was as follow: Chromatographic column: Philomon Chirex 3126 (D)-Penicillamine 250 nm*4.6 nm, 5 μm; mobile phase, 5% (v/v) acetonitrile and 95% (v/v) 2.0 mM, CuSO 4 aqueous solution; flow rate, 0.8 mL/min; detection wavelength, 254 nm [22].…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
“…The lamellar structure can provide more attachment points for laccase and facilitate the immobilization of laccase molecules. 34 The sponge-like pore structure is beneficial for the transfer of the substrate components and can improve the reaction rate between laccase and substrate. In addition, the element mapping of the Lac@Ce-GMA-Cu-DA@AS biocatalyst showed that C, N, O, and Cu elements were evenly distributed in its beads.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%